Observation of the narrow state X(3872)-->J/psipi+pi- in pp collisions at sqaure root of s=1.96 TeV. - Acosta, D; Affolder, T; Ahn, M; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2004)
We report the observation of a narrow state decaying into J/psipi+pi- and produced in 220 pb(-1) of p p-bar collisions at =1.96 Tesqaure root of sV in the CDF II experiment. We observe 730+/-90 decays. The mass is measured to be 3871.3+/-0.7(stat)+/-0.4(syst) MeV/c2, with an observed width consistent with the detector resolution. This is in agreement with the recent observation by the Belle Collaboration of the X(3872) meson.